The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.nuclphysa.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic yield in cold binary fission of even–even 244–258Cf isotopes

Abstract: The cold binary fission of even-even [244][245][246][247][248][249][250][251][252][253][254][255][256][257][258] Cf isotopes has been studied by taking the interacting barrier as the sum of Coulomb and proximity potential. The favorable fragment combinations are obtained from the cold valley plot (plot of driving potential vs. mass number of fragments) and by calculating the yield for charge minimized fragments. It is found that highest yield for 244,246,248 Cf isotopes are for the fragments with isotope of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Researchers have usually calculated the spontaneous fission half-lives [46][47][48] and Relative mass yields [21,23,49] for even-even elements with WKB model. In one of the modified statistical scission-point mode [18], the mass yield values are significantly different compared to the experimental data (more than 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have usually calculated the spontaneous fission half-lives [46][47][48] and Relative mass yields [21,23,49] for even-even elements with WKB model. In one of the modified statistical scission-point mode [18], the mass yield values are significantly different compared to the experimental data (more than 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…The fission fragments mass yields were calculated using the WKB approximation model for spontaneous fission [20,21], cold fission [22,23] and ternary fission [24,25] of super-heavy nuclei and Actinides. Recently, Gao [26] calculated the spontaneous fission half-lives for heavy and super-heavy nuclei by applying a new method of numerically solving Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…The extremum values of energy at the scission point is usually used to find the atomic numbers of the fission fragments [36][37][38][39]. The exponential function is upward-sloping, so the minimum total energy at the scission point has the greatest effect in equation (2).…”
Section: The Temperature Of Fragmentsmentioning
confidence: 99%
“…Based on the liquid drop model, Bohr and Wheeler [2] developed the theory of fission. Over many years, it has been clearly observed that lowenergy fission of heavy elements with Z > 90 is one of the most complicated nuclear processes [3]. Andersson et al [4] investigated binary fission of 159 Tb and nat Ag induced by 600MeV protons, finding fission yield cross sections of 1.9mb and 1.0mb, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 3. Plot of logarithmic half-lives for isotopes of nuclei 298−300,302 120 as a function of fission fragment mass number A 1…”
mentioning
confidence: 99%